EFL IN-SERVICE TEACHERS' EFFICACY BELIEFS: FINDINGS FROM AN UNDERDEVELOPED INDONESIAN CONTEXT - Loppies, Hellien Jequelin; Patty, Jusak (Universitas Muhammadiyah Metro, 2024)
Numerous studies have significantly highlighted the importance of exploring English as a foreign language (EFL) teachers' efficacy belief in different contexts. Nevertheless, examining teachers' capability to take action in underdeveloped settings where constrained circumstances may hinder them from undertaking necessary actions for better student achievement is scarce to date. This mixed-methods study then investigated the self-efficacy beliefs of Indonesian EFL in-service teachers in the underdeveloped region of Maluku province. This study explored how teachers perceived self-efficacy influenced their pedagogical content knowledge (PCK) and instructional practices in this resource-constrained context. Data were collected from 39 teachers through the English Language Teachers' Efficacy Beliefs Questionnaire and semi-structured interviews. The findings revealed moderate levels of self-efficacy across domains like teaching knowledge, ethics, classroom management, instructional strategies, student engagement, and evaluation. Teachers faced challenges in providing effective language models, seeking professional development, and catering to diverse learner needs. Their self-efficacy beliefs shaped approaches to curriculum implementation, understanding learners, instructional delivery, and classroom practices. The underdeveloped context likely contributed to moderate self-efficacy due to limited resources and student diversity. Strengthening teacher education programs emphasizing self-efficacy, PCK, and evidence-based practices and establishing supportive professional learning communities could enhance teachers' effectiveness in fostering positive learning environments and improving English education quality in underdeveloped regions. These findings imply that targeted interventions that enhance teacher self-efficacy could be crucial in improving educational outcomes in resource-constrained settings like Maluku.